Modeling of the dissolution kinetics of arbutus wild berries-based tablets as evaluated by electric conductivity - Abbas-Aksil, Tounsia; Benamara, Salem (Universiti Kebangsaan Malaysia, 2015)
Lyophilized powder (LP) from Algerian arbutus wild berries (Arbutus unedo L.) was obtained. This present paper reports about the dissolution (releasing) properties of LP-based tablets, evaluated through the electric conductivity (EC) of distilled water which is employed as surrounding medium, at three different temperatures (291, 298 and 309 K). In addition to this, secondary physicochemical characteristics such as elementary analysis, color and compressibility were evaluated. Regarding the modeling of ionic transfer, among the three tested models, namely Peleg, Singh et al. and Singh and Kulshestha, the latter seems to be the most appropriate (R2 = 0.99), particularly in the case of compacted tablets under 2000 Pa. The temperature dependence of the dissolution process was also studied applying Arrhenius equation (R2>0.8) which allowed to deduce the activation energy, ranging from 18.7 to 21.4 kJ.mol-1 according to the model and compression force employed.